The effectiveness of Zakat in reducing poverty incident: An analysis in Kelantan, Malaysia - Mohd Ali A.F.; Rashid Z.A.; Johari F.; Ab. Aziz M.R. (Canadian Center of Science and Education, 2024)
Indexed by SCOPUS